IMPROVING THE COMMUNITY ECONOMY THROUGH TRAINING ON MARKETING STRATEGIES FOR FARMING BUSINESS PRODUCTS IN NAGARI SIKABU LUBUK ALUNG DISTRICT PADANG PARIAMAN DISTRICT - Yulistia, Yulistia; Novi yanti; Rizka Hadya; Jhon Rinaldo; Rice Haryati; Agus Sutardjo; Dina Adawiyah; Danyl Mallisza; Bakkareng, Bakkareng (Journal of Community Service, 2024)
This community service activity aims to improve the community's economy through training on marketing strategies for agricultural products in Nagari Sikabu, Lubuk Alung District, Padang Pariaman Regency. The main problems faced by farmer groups in this area are limited market access, price fluctuations, and a lack of understanding of modern marketing strategies. Therefore, this training focuses on the application of digital marketing, the use of social media, and the use of e-commerce in marketing agricultural products. The methods used in this activity include initial observation, Focus Group Discussion [FGD], digital marketing training, and assistance in implementing marketing strategies. The results of the activity showed that the participants were very enthusiastic in participating in the training, especially in discussions related to the marketing challenges they faced. In addition, participants gain new insights and skills in utilizing digital technology to expand market reach. Overall, this activity went well and provided significant benefits for farmer groups. However, further assistance is still needed so that the implementation of the marketing strategies that have been studied can run optimally and sustainably.